The efficacy of adalimumab in the treatment of uveitis (Research, Society and Development, 2024)
Uveitis is inflammation of the uveal tract. The main manifestations are ocular hyperemia, photophobia, ocular pain, blurred vision, irregular pupil and inflammatory nodules on the anterior surface of the iris. Currently, the treatment of uveitis is associated with the use of corticosteroids. Adalimumab (ADA) is a full-length human monoclonal antibody, which is involved in the intraocular inflammation cascade, being effective in suppressing uveitis, allowing a significant reduction in the immunosuppression burden and associated corticosteroid dosage. In this study, we performed a meta-analysis with the aim of evaluating the effectiveness of using ADA in the treatment of non-infectious intermediate and posterior uveitis and panuveitis. A systematic literature review study that addressed research published between 2016 and 2021. Our systematic review selected a total of 60 articles and, among these, 12 were used with different methodological approaches, with age groups and samples varied populations. Within our study, all 12 selected articles demonstrated, in general, a good efficacy and safety of biological therapy with ADA, mainly in combined therapy and aimed at the chronicity and refractoriness of the disease associated with evidence on a pattern of improvement in all or most of the outcomes assessed.